Host–Guest Hybrid Redox Materials Self‐Assembled from Polyoxometalates and Single‐Walled Carbon Nanotubes. Issue 41 (26th August 2019) - Jordan, Jack W.; Lowe, Grace A.; McSweeney, Robert L.; Stoppiello, Craig T.; Lodge, Rhys W.; Skowron, Stephen T.; Biskupek, Johannes; Rance, Graham A.; Kaiser, Ute; Walsh, Darren A.; Newton, Graham N.; Khlobystov, Andrei N.
Abstract: The development of next‐generation molecular‐electronic, electrocatalytic, and energy‐storage systems depends on the availability of robust materials in which molecular charge‐storage sites and conductive hosts are in intimate contact. It is shown here that electron transfer from single‐walled carbon nanotubes (SWNTs) to polyoxometalate (POM) clusters results in the spontaneous formation of host–guest POM@SWNT redox‐active hybrid materials. The SWNTs can conduct charge to and from the encapsulated guest molecules, allowing electrical access to >90% of the encapsulated redox species. Furthermore, the SWNT hosts provide a physical barrier, protecting the POMs from chemical degradation during charging/discharging and facilitating efficient electron transfer throughout the composite, even in electrolytes that usually destroy POMs. Abstract : Reagent‐free redox‐driven nanoconfinement of polyoxometalate clusters within single‐walled carbon nanotubes is demonstrated. The densely packed chains of the polyoxometalate (POM) anions within cationic single‐walled carbon nanotubes form spontaneously and irreversibly under ambient conditions. Protected from the external environment and effectively "wired" to the carbon support, the nanoconfined redox‐active POMs exhibit exceptional electrochemical stability, even in environments in which they cannot usually exist.